C Dots Derived from Waste of Biomass and Their Photocatalytic Activities - Haryadi Haryadi; Muhammad Ridwhan Wira Purnama; Ari Wibowo (Universitas Gadjah Mada, 2018)
Carbon nanodots (CNDs) which are part family of carbon nanoparticles have drawn a lot of attention due to their prominent characters and wide prospective applications. The materials are non-toxic and exhibit fluorescence properties that are potential for application in photocatalysis, optoelectronic, bioimaging and sensors. Various approaches of CNDs synthesis have been investigated by means of a large variety of starting materials and techniques. A green and an effective approach in gaining CNDs from wastes biomass-carbonaceous particles of a dried solid waste of cow manure have been employed by hydrothermal treatment. The CNDs were then attained after carbonaceous particles dissolution step under microwave irradiation. The temperature range of hydrothermal treatment was in between 250 to 300 °C. The formation of C=C, C-O bonds, and conjugated structures has been observed by FTIR and photoluminescence properties have been identified under 366 nm of UV irradiation. Furthermore, the morphology of as-synthesized CNDs was investigated by HR-TEM and crystallinity was observed by X-Ray Diffraction (XRD). Photocatalytic degradation of synthetic dye solution of methylene blue (MB) in the presence of carbon dots has been investigated under visible light.